Unemployment in the Russian Federation against the background of foreign sanctions - S. A. Mamiy; T. A. Bochkova (Новые технологии)
Changes of various kinds in recent months related to the redistribution of supply chains in the world market, as well as the withdrawal of foreign companies and the imposition of Western sanctions, have led to a variety of problems in our country that require immediate solutions. The main social and economic problem in the current situation is the unemployment increase. This factor has an extremely negative impact on various spheres of human life and society as a whole. The underutilization of human resources leads to a decrease in potential GDP and national income. Also in this situation, an individual suffers, as his/her income is reduced, which entails a decrease in demand in the market. This kind of situation will complicate the existence of various types of business, which again can lead to a decrease in the number of employed population. The research has been conducted in order to identify the consequences that have occurred or may occur as a result of foreign sanctions and the withdrawal of corporations from the Russian market. The way the state is struggling with the main problems is sponsoring domestic enterprises and indexing various types of payments to citizens and increasing the number of employees. During the research, the following scientific methods have been used: induction, analysis, synthesis, comparison, abstraction. The result of the presented article is the conclusion that, of course, the sanctions imposed against the Russian Federation cause damage to the state economy. In any case, unemployment will rise this year, but this increase will not be critical. Timely introduced support measures from the government help to stabilize the situation. Thus, economic indicators will return to normal level next year, by this time new supply chains will be established, and new enterprises will begin to appear that can provide people with work.